Enhancing Green HRM Practices for Sustainable Business Growth and Boosting Employee Engagement: A Case Study of Star-Rated Hotels - Nischaya Hulu; Dyah Palupiningtyas (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This study examines the implementation of Green Human Resource Management (Green HRM) strategies in star-rated hotels in Semarang Regency, Indonesia, and their impact on sustainable business practices and employee engagement. Employing a mixed-method approach, the study involved a survey of 35 star-rated hotels and in-depth interviews with 15 senior managers. Results reveal significant variations in Green HRM implementation, with a positive correlation between hotel size and implementation level. Regression analysis and Structural Equation Modeling (SEM) demonstrate the positive impact of Green HRM on business sustainability indicators and employee engagement. Key challenges in implementation include resistance to change and difficulties in measuring short-term ROI, while opportunities encompass enhanced brand competitiveness and operational efficiency. This research contributes theoretically to the contextualization of Green HRM in the hospitality industry of non-metropolitan areas and provides practical implications for hotel managers and policymakers in adopting practices that support business sustainability and enhance employee engagement.